Implementing Non-Value-Added Time as an Indicator of Patient Satisfaction in a Student Run Free Clinic - Liu, Benjamin; Brown, Miranda; Bennett, Alexandra; Samant, Samira; Lundh, Rebecca; Ferguson, Catherine (Journal of Student-Run Clinics, 2022)
Improving patient satisfaction in a student-run free clinic setting presents unique challenges as free clinics often receive very high patient satisfaction scores. It may seem odd to label this “a problem”; however, this phenomenon may mask patient concerns and impede a clinic’s abilities to measure the effect of interventions on patient satisfaction. In this article we detail our experience with addressing patient satisfaction in a student-run free clinic, the approach we took, key lessons learned, and recommendations for future clinics creating project goals aimed at improving patient satisfaction.